1990
DOI: 10.2169/internalmedicine1962.29.138
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immunity in myasthenia gravis after thymectomy and corticosteroid therapy.

Abstract: Clinical and immunological changes in patients with myasthenia gravis (MG) who had extended thymectomy (Tx) and/or corticosteroid therapy were examined to elucidate the mechanisms of improvement following the treatments. The changes found were: 1) After Tx and steroid therapy, in patients with MG whoshowed clinical improvement, the CD4/CD8 ratio and B lymphocyte subpopulations were markedly decreased. 2) Linear correlations between two T-cell subsets were evident in CD3against CD4 and CD4/CD8 against CD4after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Previous data on corticosteroid therapy in MG showed a general decrease of B cells in MG which was not observed in this study [29]. Similar to the present study, higher frequency of CD27 + memory and lower frequency of CD27 À naïve B cell subsets have recently been demonstrated in AChR-MG patients treated with IS or longterm disease [30].…”
Section: Discussionsupporting
confidence: 86%
“…Previous data on corticosteroid therapy in MG showed a general decrease of B cells in MG which was not observed in this study [29]. Similar to the present study, higher frequency of CD27 + memory and lower frequency of CD27 À naïve B cell subsets have recently been demonstrated in AChR-MG patients treated with IS or longterm disease [30].…”
Section: Discussionsupporting
confidence: 86%
“…Immunosuppressed individuals, such as transplant patients, are known to have an increased risk of malignancies; 9 however, several series have indicated that thymectomy dose not influence immunoparameters in patients with thymoma and myasthenia gravis. 10,11 Moreover, the extrathymic malignancies were often diagnosed before or at the same time as thymoma. Therefore, the precise mechanism of these types of malignancies remains unclear.…”
Section: Case Reportmentioning
confidence: 99%